AB0420 Secondary Efficacy Outcomes from a Phase 3 Study Support Clinical Equivalence Between BOW015 and Infliximab in Patients with Active Rheumatoid Arthritis on Stable Methotrexate Doses. (9th June 2015) - Kay, J.; Chopra, A.; Chandrashekara, S.; Olakkengil, D.; Bhojani, K.; Bhatia, G.; Rathi, G.; Thomas, M.; Maroli, S.; Thomson, E.; Lassen, C.; Shneyer, L.; et al.
Abstract : Background: BOW015 is being developed as a biosimilar of reference infliximab (rIFX, Remicade®). Therapeutic equivalence of BOW015 and rIFX was evaluated in patients with active rheumatoid arthritis (RA) in a 54-week (wk) Phase 3 comparative effectiveness study. ACR20 responses and safety and immunogenicity data have been reported. 1, 2 Here, we report the secondary efficacy endpoints for this study. Objectives: To determine whether efficacy of BOW015 is equivalent to that of rIFX when each is administered in combination with methotrexate (MTX). Methods: In this double-blind (DB), active comparator study, 189 patients with RA (87.8% female; mean age, 44.8 years) receiving stable MTX doses (10-20 mg/wk) were randomized 2:1 to receive either BOW015 or rIFX 3 mg/kg IV at wks 0, 2, 6 and 14. In the open-label (OL) phase, responders to BOW015 or rIFX (n=157) received BOW015 3 mg/kg IV every 8 wks at wks 22, 30, 38 and 46, with follow-up at wk 54. ACR20/50/70 responses, CRP, ESR, tender and swollen joint counts, subject pain assessment and subject and physician global assessment of disease activity (each by VAS 0-10 cm) were evaluated at multiple time points. Results: Baseline values were similar for subjects in both treatment arms. At the end of the DB phase (wk 16), BOW015 and rIFX each produced clinically significant improvement from baseline in all secondary endpoints (see table ). There was no significant difference in the proportion of subjects achieving ACR20, 50, or 70 responses between treatment groups; these remained stable throughout the OL phase, demonstrating long-term durability of the response to BOW015, including that for the rIFX responders who switched to BOW015 at wk 22. At the end of the OL phase (wk 54), mean improvements in CRP, ESR, and tender and swollen joint counts were similar to those obtained at wk 16 and again did not differ significantly between treatment arms, supporting durability of response. Mean VAS scores for subject pain assessment and for both subject and physician global assessment also did not differ significantly between treatment arms at wk 54 and were lower than those reported at wk 16, consistent with further improvement during the OL phase. Conclusions: Efficacy of BOW015 and rIFX are equivalent, as assessed at wk 16 both by the primary endpoint of ACR20 and by secondary efficacy outcomes. Durability of response to BOW015 has been demonstrated over 54 wks. Taken in combination with analytical, pharmacokinetic, and safety data, these results establish biosimilarity between BOW015 and rIFX. References: Kay J et al. Ann Rheum Dis 2014; 73(Suppl2):64. Kay J et al. Arthritis Rheumatol. 2014; 66(12):3538. Acknowledgements: This research was sponsored by EPIRUS Biopharmaceuticals Inc. Disclosure of Interest: J. Kay Grant/research support from: AbbVie Inc.; Eli Lilly and Company; Pfizer Inc.; Roche Laboratories, Inc. (paid to the University of Massachusetts Medical School), Consultant for: Amgen, Inc.; AbbVie Inc.; AstraZeneca; Boehringer Ingelheim GmbH; Bristol-Myers Squibb Company; Eli Lilly and Company; Epirus Biopharmaceuticals Inc.; Genentech Inc.; Hospira, Inc.; Janssen Biotech, Inc.; Merck Sharp & Dohme Corp.; Nippon Kayaku Co., Ltd.; Novartis Pharmaceuticals Corporation; Pfizer Inc.; Samsung Bioepis; Roche Laboratories, Inc.; UCB, Inc., A. Chopra Consultant for: Epirus Biopharmaceuticals Inc.; Reliance Life Sciences, S. Chandrashekara Grant/research support from: Epirus Biopharmaceuticals Inc.; Reliance Life Science; Biolcon; Pfizer Inc., D. Olakkengil: None declared, K. Bhojani: None declared, G. Bhatia: None declared, G. Rathi: None declared, M. Thomas: None declared, S. Maroli: None declared, E. Thomson Consultant for: Epirus Biopharmaceuticals Inc., C. Lassen Employee of: Epirus Biopharmaceuticals Inc., L. Shneyer Shareholder of: Merck, M. Wyand Employee of: Epirus Biopharmaceuticals Inc.